Optimal Economic Ordering Policy with Trade Credit and Discount Cash-Flow Approach - Hao Jiaqin; Mo Jiangtao; Min Jie (Universitas Ahmad Dahlan, 2015)
In this paper, an inventory model for deteriorating items under two levels of trade credit will be established. The trade credit policy depends on the retailer’s order quantity. When the retailer’s order quantity is greater than or equal to a predetermined quantity, both of the supplier and the retailer are taking trade credit policy; otherwise, the delay in payments is not permitted. Since the same cash amount has different values at different points of time, the discount cash-flow (DCF) is used to analysis the inventory model. The purpose of this paper is to find an optimal ordering policy to minimizing the present value of all future cash-flows cost by using DCF approach. The method to determine the optimal ordering policy efficiently is presented. Some numerical examples are provided to demonstrate the model and sensitivity of some important parameters are illustrated the optimal solutions.